Impact of transition metal oxidation state on the multiferroic properties and magnetoelectric coupling strength of BST ceramics. Issue 3 (2nd July 2020) - Chawla, Aanchal; Singh, Anupinder; Babu, P. D.; Singh, Mandeep
ABSTRACT: Effect of starting Fe precursor (Fe2 O3 and Fe3 O4 ) on the multiferroic properties of BST (Ba0.96 Sr0.04 Ti0.91 Fe0.09 O3 ) ceramics has been investigated. Considerable changes in the ferroelectric and magnetic properties of these ceramics were observed. High crystallinity, tetragonal structure and phase purity of both the samples were confirmed using X-ray diffraction analysis. The field emission scanning electron microscopy analysis confirmed the uniform grain growth in both the samples with an average grain size of ≈0.40 μm. X-ray photoelectron spectroscopy analysis confirmed the presence of Fe 2+ only and both Fe 2+ and Fe 3+ in Fe2 O3 - and Fe3 O4 -doped samples. The Fe3 O4 -doped BST samples displayed higher Pr and Mr values (2.32 μC/cm 2 and 0.012 emu/g) as compared to Fe2 O3 -doped BST samples. The M-E coupling response (≈10.56%) too was observed to be more pronounced in Fe3 O4 -doped BST samples. Our research work suggests that Fe3 O4 doping in BST is better suited for multiferroic applications due to the presence of multivalent Fe ions.